Folosim formula de calcul prescurtat
[tex]\boxed{\boldsymbol{(a - b)(a + b) = a^{2} - b^{2}}}[/tex]
① (3-√6)(3+√6) = 3² - (√6)² = 9 - 6 = 3
② (√3-1)(√3+1) = (√3)² - 1² = 3 - 1 = 2
③ (3-√5)(3+√5) = 3² - (√5)² = 9 - 5 = 4
Suma devine:
(3-√6)(3+√6)+(√3-1)(√3+1)-(3-√5)(3+√5) =
= 3 + 2 - 4
= 5 - 4
[tex]=\bf 1[/tex]
______
Formule de calcul prescurtat:
[tex]\boxed{\boxed{\boldsymbol{(a \pm b)^{2} = a^{2} \pm 2ab + b^{2}}} \ \ \boxed{\boldsymbol{(a - b)(a + b) = a^{2} - b^{2}}}}\\[/tex]
______
https://brainly.ro/tema/10776449